2017
DOI: 10.1097/nne.0000000000000365
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Mass Casualty Incident Simulation Design Protocol to Prepare Prelicensure Nursing Students to Respond to a Disaster

Abstract: Nurses need to be prepared to respond to mass casualty incidents. Simulation is an ideal teaching intervention that can be used to prepare nursing students to effectively triage patients and allocate limited resources. This article describes a detailed interprofessional mass casualty simulation of a bus crash with 32 victims. Nursing students trained with emergency responders with students acting as charge nurses throughout the simulation. The details of the simulation are provided for faculty to replicate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 5 publications
0
16
0
1
Order By: Relevance
“…41 Defined as "when students from 2 or more professions learn about, from, and with each other to enable effective collaboration and improve health outcomes," this is termed interprofessional education (IPE), and studies have shown effectiveness in increasing confidence and collaboration. 27,40,42,43 This may be particularly important, as prior work by Markenson et al, found that students perceived less competence and confidence compared with their actual knowledge assessed by survey. This, combined with reported discomfort working with other health-care providers could be addressed through IPE.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…41 Defined as "when students from 2 or more professions learn about, from, and with each other to enable effective collaboration and improve health outcomes," this is termed interprofessional education (IPE), and studies have shown effectiveness in increasing confidence and collaboration. 27,40,42,43 This may be particularly important, as prior work by Markenson et al, found that students perceived less competence and confidence compared with their actual knowledge assessed by survey. This, combined with reported discomfort working with other health-care providers could be addressed through IPE.…”
Section: Discussionmentioning
confidence: 98%
“…Where possible, curriculum that brings together students from varied health-care schools can take advantage of the strengths each school can bring, as well as making students more aware of the roles each practitioner brings. 40 Furthermore, it has been suggested that the mental health of the community may benefit from the inclusion of community cooperation in disaster recovery efforts. 41 Defined as "when students from 2 or more professions learn about, from, and with each other to enable effective collaboration and improve health outcomes," this is termed interprofessional education (IPE), and studies have shown effectiveness in increasing confidence and collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation has become a standard of education and training in the current medical environment for multiple reasons, including patient safety initiatives as well as practising high stakes low frequency events such as disaster triage training. 25 34–37 Over the past decade, multiple studies have been published looking at effectiveness, cost analysis and financial savings from simulation training. 38 For example, studies in regular simulated paediatric mock codes and simulation-based obstetric emergencies have evaluated patient outcomes as well as the ultimate financial savings to demonstrate value and necessity in such training.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation training drills should be included when creating a response plan for MCIs, as this training not only provides an opportunity for multidisciplinary feedback but allows for staff members to test the emergency response plan [13,[16][17][18][19][20][21][22][23][24][25][26][27]. There are different types of simulation, which include skill development in a controlled environment or practice in the clinical space, called in situ simulations.…”
Section: Role Of Simulationmentioning
confidence: 99%
“…Simulation has been found to be an effective training model to increase MCI preparedness [13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Role Of Simulationmentioning
confidence: 99%